Flavonoids from the flowers of Impatiens glandulifera Royle isolated by high performance countercurrent chromatography. Issue 2 (11th January 2016) - Vieira, Mariana N.; Winterhalter, Peter; Jerz, Gerold
Abstract: Introduction: Impatiens glandulifera Royle (Balsaminaceae) is an annual herb from the Himalaya region, currently widespread along European river systems and one of the most important neophyte invading plants in Germany. Exploring the effects of allelopathic plant chemicals is important for the understanding of its ecological impacts in the process of suppression of indigenous plant species. Objective: To investigate the chemical composition of Impatiens glandulifera flowers (IGFs) using high performance countercurrent chromatography (HPCCC). Methods: The flowers of Impatiens glandulifera were manually separated and extracted with ethanol. LC‐ESI‐MS/MS was used to characterise the crude extract of IGF. The various flavonoids detected were isolated by HPCCC using of methyl tert‐ butyl ether–acetonitrile–water (2:2:3, v / v / v ). The combination of the data provided by preparative ESI‐MS/MS metabolite profiling, LC‐ESI‐MS/MS, UV‐vis and 1D/2D‐NMR spectroscopic analysis was used to elucidate the structures of the isolated compounds. Results: HPCCC runs led to the direct isolation of pure dihydromyricetin (ampelopsin), eriodictyol‐7‐ O ‐glucoside, kaempferol‐3‐ O ‐glucoside (astragalin) and kaempferol‐3‐ O ‐6ʺ‐malonyl‐glucoside, as well as the pre‐purification of kaempferol‐3‐ O ‐rhamno‐rhamnosyldiglucoside, quercetin‐3‐ O ‐galactoside (hyperoside), quercetin and kaempferol in a single step. Conclusion: This is the first report on the flavonoid composition of the species Impatiens glandulifera . The developed protocol was successfully used to isolate the main flavonoids from the crude extract of IGFs. This combined HPCCC and HPLC procedure could be applied to the fast fractionation and recovery of flavonoid derivatives of other plant extracts. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Impatiens glandulifera (Balsaminaceae) is one of the most important neophyte invading plant in Germany. Therefore, the aim of this work was to investigate the chemical composition of its flowers using high performance countercurrent chromatography (HPCCC). HPCCC runs lead to the isolation of dihydromyricetin, eriodictyol‐7‐ O ‐glucoside, kaempferol‐3‐ O ‐glucoside and kaempferol‐3‐ O ‐6″‐malonyl‐glucoside, as well as the pre‐purification of kaempferol‐3‐ O ‐rhamnosyldiglucoside, quercetin‐3‐ O ‐galactoside, quercetin and kaempferol in a single step. The combination of ESI‐MS/MS metabolite profiling, LC‐ESI‐MS/MS, UV‐Vis and 1D/2D‐NMR data allowed the identification of the isolated compounds.